2022
DOI: 10.1111/jpn.13781
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants status and physiological responses to early and late heat stress in two rabbit breeds

Abstract: Early life heat stress negatively affects rabbit production and well‐being. However, the physiological response to acute heat stress in later life is not clearly defined. The present study aims to investigate the effects of early and late heat stress at 36°C on some blood constituents, antioxidant enzymes activity in the blood, and muscle in New Zealand white and Baladi Black rabbits. A total of sixty post‐weaning rabbits of each breed were randomly divided into two groups; control groups (NZWC and BBC) and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…Under thermoneutral conditions, antioxidative enzymes such as SOD and GSH are capable of scavenging reactive oxygen species to modulate redox status and dynamic balance. In agreement with our findings, both Saghir et al and Madkour et al pointed out that the rabbits’ plasma concentrations of SOD and GSH declined with the increasing house temperature while the level of MDA was elevated, which was linked to progressive oxidative stress [ 27 , 28 ]. Simultaneously, considering the intimate relationship between oxidative stress and inflammation responses, we noted that the levels of pro-inflammatory cytokines such as IL-1α, IL-1β, and IL-2 were increased.…”
Section: Discussionsupporting
confidence: 93%
“…Under thermoneutral conditions, antioxidative enzymes such as SOD and GSH are capable of scavenging reactive oxygen species to modulate redox status and dynamic balance. In agreement with our findings, both Saghir et al and Madkour et al pointed out that the rabbits’ plasma concentrations of SOD and GSH declined with the increasing house temperature while the level of MDA was elevated, which was linked to progressive oxidative stress [ 27 , 28 ]. Simultaneously, considering the intimate relationship between oxidative stress and inflammation responses, we noted that the levels of pro-inflammatory cytokines such as IL-1α, IL-1β, and IL-2 were increased.…”
Section: Discussionsupporting
confidence: 93%
“…Our study exhibited noteworthy decreases in the concentrations of pro-inflammatory cytokines (IFN-γ and IL-4) in the NCEO-supplemented rabbits compared to the control, indicating the potent anti-inflammatory activities of NCEO. On the other hand, the dietary treatment resulted in a significant increase in the concentration of NO, which is a small molecule that plays an indispensable role under physiological concentrations in defense against pathogens and thermos-tolerance during heat stress, as it has a decisive role in the vasodilation of the blood vessels of the skin [ 48 , 56 , 57 ]. Moreover, mounting evidence suggests that NO plays other roles in neurotransmission and immune regulation [ 7 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies revealed that the plasma concentration of GSH-Px, SOD, and CAT was significantly minimized, while the plasma level of MDA was elevated in heat-stressed rabbits [84,85]. Likewise, Madkour et al [86] observed that HS at 36 • C lessened the amounts of SOD, GSH, and CAT, and elevated the MDA concentration in the blood plasma and muscle of broiler rabbits. Bai et al [79] postulated that the plasma total antioxidant capacity (TAC) concentration was reduced in growing rabbits under HS conditions.…”
Section: Effect Of Hs On Antioxidative Propertiesmentioning
confidence: 97%
“…Additionally, in fattening rabbits exposed to HS, the serum lysosome activity and nitric oxide levels were reduced [34]. Moreover, HS disturbed the equilibrium between anti-inflammatory and pro-inflammatory cytokines [34], which might be connected with a progressive inflammation response [86]. Abdel-Latif et al [39] observed that HS had a negative influence on IFN-γ, TNF-α, and heat shock protein 70 (HSP70) expression leading to affect the infiltration of regulatory T cells adversely and NK cells in New Zealand White (NZW) growing rabbits.…”
Section: Effect Of Hs On Immune Responsivenessmentioning
confidence: 99%